The Study of Hematological Parameters of Animals in the Application of Enterosorbent Food Fiber - G. Tussupbekova; Z. Yessimsiitova; N. Ablaikhanova; A. Rakhmetova; G. Alshynbekova; S. Tuleukhanov; Z. Zhussupbekova; G. Ashimhanova; Y. Kuandykov (Journal of Pharmacy and Nutrition Sciences, 2019)
One of the most important issues is the study of healthy nutrition of the population of Kazakhstan. Proper nutrition provides growth, contributes to the prevention of diseases, increase efficiency and prolong life of people, while creating conditions for adequate adaptation to the environment. A large part of the population of Kazakhstan as a result of technological processing, the use of inferior in chemical composition of food raw materials, the influence of other causes, does not receive the necessary amount of essential components of food, which lead to illness, premature old age and shortened life. The situation is aggravated by the low cultural level of the population in terms of good nutrition and the lack of skills to lead a healthy lifestyle. The problem of quality and food safety, while food must have not only nutritional and physiological value, but also perform preventive functions.